Polymorphisms of the TLR2 and TLR4 genes are associated with risk of gastric cancer in a Brazilian population - de Oliveira, Juliana Garcia [UNESP]; Silva, Ana Elizabete [UNESP] (Baishideng Publ Grp Co Ltd, 2012)
AIM: To investigate toll-like receptor 2 (TLR2) -196 to -174 del, and TLR4 (+896A/G rs4986790 and +1196C/T rs4986791) polymorphisms at risk of chronic gastritis and gastric cancer in a Brazilian population and association of gastric lesions with risk factors such as smoking, alcohol intake and Helicobacter pylori infection.METHODS: In this case-control study, polymorphism at TLR2 496 to -174 del was investigated by using the polymerase chain reaction (PCR) method, while the PCR-restriction fragment length polymorphism technique was carried out to identify the TLR4 (rs4986790 and rs4986791) genotypes in 607 Brazilian individuals (208 with chronic gastritis-CG, 174 with gastric cancer-GC and 225 controls -C).RESULTS: The single nucleotide polymorphisms TLR4+1196C/T was not associated with risk of chronic gastritis or gastric cancer and the homozygous genotypes TLR4+896GG and TLR4+1196TT were absent in the studied population. However, the frequency of TLR2 -196 to -174 ins/del + del/del and TLR4+896AG genotypes was significantly higher (P < 0.01 and P = 0.01, respectively) in the cancer group (33.4% and 11.5%, respectively) than in the control group (16.9% and 4.5%, respectively). It was also observed that the G-C haplotype of the TLR4+896A/G+1196C/T (P = 0.02) and the combination of variant alleles of the TLR2/TLR4+896G (P = 0.02) are associated with susceptibility to gastric cancer. In addition, the multiple logistic regression showed that male gender [odds ratio (OR) = 2.70; 95% CI: 1.66-4.41; P < 0.01], alcohol intake (OR = 2.93; 95% CI: 1.76-4.87; P < 0.01), TLR2 -196 to -174 del (OR = 2.64; 95% CI: 1.56-4.44; P < 0.01) and TLR4+896G (OR = 3.19; 95% CI: 1.34-7.61; P < 0.01) polymorphisms were associated with a higher susceptibility to developing this neoplasm.CONCLUSION: Our data indicate that TLR2 -196 to -174 del and TLR4+896G may increase the risk of gastric cancer in a Brazilian population. (C) 2012 Baishideng. All rights reserved.
Keywords: Polymorphism; Toll-like receptor 2; Toll-like receptor 4; Gastric cancer; Gastritis